BIRC7 is Beneficial for Melanoma Progression and Hypoxic Response - Xu H; Liu H; Li Z; Xu Q; Lin N; Li X (Dove Medical Press, 2022)
Haiting Xu,1 Huazhen Liu,2 Zi Li,3 Qin Xu,3 Nan Lin,1 Xiaoyang Li1 1Department of Hand and Plastic Surgery, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325027, People's Republic of China; 2Department of Burn, Changhai Hospital Affiliated Naval Medical University, Shanghai, 200433, People's Republic of China; 3Department of Dermatology, the Second School of Medicine, Wenzhou Medical University, Wenzhou, Zhejiang, 325027, People's Republic of ChinaCorrespondence: Xiaoyang Li, Department of Hand and Plastic Surgery, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325027, People's Republic of China, Email lixioayang1166@163.comBackground: Cutaneous melanoma (CM) accounts for about 90% of all melanoma cases. HIF-1α overexpression is associated with poor prognosis in many cancers including CM. Hence, we characterized differentially expressed genes (DEGs) in the response of CM cells to normoxia and hypoxia.Methods: We first successfully constructed cell hypoxia model and then performed RNA-seq to explore the changes of gene transcription in CM cells during hypoxia. The highest expression of the six genes was detected using qRT-PCR and Western blot assays. The binding sites between BIRC7 promoter and HIF-1α was explored by luciferase assay. Cellular function assays were used to observe the role of BIRC7 in the effect of hypoxia on tumor progression.Results: Compared with the transcriptome data of the control group, a total of 2601 DEGs were identified in the hypoxic group. There were 1517 genes with significantly higher expression and 1084 genes with lower expression in the hypoxic group. Among them, OSCAR, BIRC7, HBA1, SFN, GOLT1A, and BEX2 were significantly up-regulated in the hypoxic group. BIRC7 expression was most significantly up-regulated and a downstream factor of HIF-1α. We highlighted that knockdown of BIRC7 reversed the positive effects of HIF-1α on A875 and M14 cells.Conclusion: Our findings demonstrated that BIRC7 was a downstream factor of HIF-1α and reversed the effect of hypoxia on promoting tumor progression of CM cells.Keywords: apoptosis, BIRC7, HIF-1α, hypoxia, malignant melanomas